Mechanical properties of recycled aggregates concrete with sisal fiber and silica fume. (2022) - Vijayan, Vishnu; Jayakesh, K.; Anand, K.B.
Abstract: Concrete is a heavily reliant material in the field of construction with aggregates the key ingredient. In construction, various practices like renovation, updating of new rules in construction, obsolescence and demolition leads to the accumulation of large quantity of wastes. Mainly it contains large amount of concrete contents which are considered as solid waste. It necessitates the importance of research for the management of these solid wastes, particularly construction and demolition (C&D) wastes. By converting them for the new construction purposes we can effectively use these type of waste materials. The government would incur colossal losses and the ecosystem will suffer greatly degrading the sustainability of concrete. Hence in this research, the objective was chosen to recycle the old Concrete waste as coarse aggregate with different grades to prepare new mixes in M30 mix design. We can solve the impact of these wastes by strengthening and reutilizing the demolished wastes by adding sisal fibres with silica fumes as admixtures to the recycled aggregate concrete to improve the mechanical properties of the RAC. The effective usage of the demolished Construction waste can reduce the environmental consequences to a great extent as well as the transformation of waste materials into aggregates helps to overcome the problem of material scarcity in the field of construction. As we know, in case of rigidity and strength the name concreate comes as ultimate, so that reusing the used concrete aggregate helps in various fields under cost effectively.